COOPERATIVE SECURITY: CONFIDENCE-BUILDING MEASURES WITH BRAZIL IN TIMES OF ARGENTINIAN DEMOCRACY - Doval, Gisela Pereyra; Varela, Miguela (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2022)
The article applies the Cooperative Security approach to the bilateral relation between Argentina and Brazil through the development of Confidence-Building Measures as elements that generate mechanisms of long-term cooperation. The aim is to review bilateral cooperation in the nuclear field.